(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
Presupposition and tagmanship are important concepts of pragmatic linguistics in Uzbek linguistics, and their differential signs play a key role in analyzing the hidden meaning of a sentence. In this article, the specific features and differential signs of the phenomenon of presupposition and tagmanship are studied and illustrated with examples.